2021
DOI: 10.1002/wrna.1660
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the right exit: How functional plasticity of the nuclear pore drives selective and efficient mRNA export

Abstract: The nuclear pore complex (NPC) serves as a central gate for mRNAs to transit from the nucleus to the cytoplasm. The ability for mRNAs to get exported is linked to various upstream nuclear processes including co-transcriptional RNP assembly and processing, and only export competent mRNPs are thought to get access to the NPC. While the nuclear pore is generally viewed as a monolithic structure that serves as a mediator of transport driven by transport receptors, more recent evidence suggests that the NPC might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 134 publications
(231 reference statements)
0
13
0
Order By: Relevance
“…These and other findings collectively highlight the role of the NB in tethering the genome and regulating its activity. Moreover, TPR and Mlps are also capable of recruiting mRNPs and the TREX-2 (Transcription Elongating and RNA Export) mRNA export complex, presumably to facilitate mRNA processing and export following active transcription at the NB [27][28][29]. Supporting this notion, mutations in TPR and Mlp1/2p lead to nuclear retention of mis-spliced or aberrant mRNAs [30][31][32].…”
Section: Introductionmentioning
confidence: 92%
“…These and other findings collectively highlight the role of the NB in tethering the genome and regulating its activity. Moreover, TPR and Mlps are also capable of recruiting mRNPs and the TREX-2 (Transcription Elongating and RNA Export) mRNA export complex, presumably to facilitate mRNA processing and export following active transcription at the NB [27][28][29]. Supporting this notion, mutations in TPR and Mlp1/2p lead to nuclear retention of mis-spliced or aberrant mRNAs [30][31][32].…”
Section: Introductionmentioning
confidence: 92%
“…This is likely a consequence of regulatory proteins binding to the 3 UTR and slowing export or actively retaining mRNA transcripts within the nucleus. Such mechanisms are likely to occur also in yeast, where nuclear traffic is highly regulated [17].…”
Section: Cis-regulatory Featuresmentioning
confidence: 99%
“…However, recent findings in both animals and yeast have shown that the NPC plays a role in both active and repressive activities, with certain NPC components or subcomplexes preferentially affecting gene activation or silencing [ 13 ]. Interestingly, the nuclear pore exhibits high heterogeneity at distinct nuclear subdomains even in a single cell, which might be required for organization of chromatin compartmentalization and transport of specific cargos [ 96 ]. Taken together, the NPC is clearly a dynamic assembly, with both highly flexible composition and conformation, that accommodates its roles in cargo transport, genome activities and beyond.…”
Section: The Npc Bridges Nuclear Transport and Gene Regulationmentioning
confidence: 99%